The Full Wiki

Continuum mechanics/Polar decomposition: Wikis

Advertisements

Note: Many of our articles have direct quotes from sources you can cite, within the Wikipedia article! This article doesn't yet, but we're working on it! See more info or our list of citable articles.

Study guide

Up to date as of January 14, 2010

From Wikiversity

Contents

Polar decomposition

The w:Polar decomposition theorem states that any second order tensor whose determinant is positive can be decomposed uniquely into a symmetric part and an orthogonal part.

In continuum mechanics, the deformation gradient \boldsymbol{F} is such a tensor because \det(\mathbf{f}) > 0. Therefore we can write

 \boldsymbol{F} = \boldsymbol{R}\cdot\boldsymbol{U} = \boldsymbol{V}\cdot\boldsymbol{R}

where \boldsymbol{R} is an orthogonal tensor (\boldsymbol{R}\cdot\boldsymbol{R}^T = \boldsymbol{\mathit{1}}) and \boldsymbol{U}, \boldsymbol{V} are symmetric tensors (\boldsymbol{U} = \boldsymbol{U}^T and \boldsymbol{V} = \boldsymbol{V}^T) called the right stretch tensor and the left stretch tensor, respectively. This decomposition is called the polar decomposition of \boldsymbol{F}.

Recall that the right Cauchy-Green deformation tensor is defined as

 \boldsymbol{C} = \boldsymbol{F}^T\cdot\boldsymbol{F}

Clearly this is a symmetric tensor. From the polar decomposition of \boldsymbol{F} we have

 \boldsymbol{C} = \boldsymbol{U}^T\cdot\boldsymbol{R}^T\cdot\boldsymbol{R}\cdot\boldsymbol{U} = \boldsymbol{U}\cdot\boldsymbol{U} = \boldsymbol{U}^2

If you know \boldsymbol{C} then you can calculate \boldsymbol{U} and hence \boldsymbol{R} using \boldsymbol{R} = \boldsymbol{F}\cdot\boldsymbol{U}^{-1}.

Advertisements

How do you find the square root of a tensor?

If you want to find \boldsymbol{U} given \boldsymbol{C} you will need to take the square root of \boldsymbol{C}. How does one do that?

We use what is called the spectral decomposition or eigenprojection of \boldsymbol{C}. The spectral decomposition involves expressing \boldsymbol{C} in terms of its eigenvalues and eigenvectors. The tensor product of the eigenvectors acts as a basis while the eigenvalues give the magnitude of the projection.

Thus,

 \boldsymbol{C} = \sum_{i=1}^3 \lambda_i^2~ \boldsymbol{N}_i\otimes\boldsymbol{N}_i

where \lambda_i^2 are the principal values (eigenvalues) of \boldsymbol{C} and \boldsymbol{N}_i are the principal directions (eigenvectors) of \boldsymbol{C}.

Therefore,

 \boldsymbol{U}^2 = \sum_{i=1}^3 \lambda_i^2~ \boldsymbol{N}_i\otimes\boldsymbol{N}_i

Since the basis does not change, we then have

 \boldsymbol{U} = \sum_{i=1}^3 \lambda_i~ \boldsymbol{N}_i\otimes\boldsymbol{N}_i

Therefore the λi can be interpreted as principal stretches and the vectors \boldsymbol{N}_i are the directions of the principal stretches.

Exercise:

If

 \boldsymbol{U} = \sum_{i=1}^3 \lambda_i~ \boldsymbol{N}_i\otimes\boldsymbol{N}_i

show that

 \boldsymbol{U}^2 = \boldsymbol{U}\cdot\boldsymbol{U} = \sum_{i=1}^3 \lambda_i^2~ \boldsymbol{N}_i\otimes\boldsymbol{N}_i ~.

Example of polar decomposition

Let us assume that the motion is given by

 \begin{align} x_1 &= \cfrac{1}{4} \left[4~X_1 + (9 - 3~X_1 - 5~X_2 - X_1~X_2)~t\right] \ x_2 &= X_2 + (4 + 2~X_1)~t \end{align}

The adjacent figure shows how a unit square subjected to this motion evolves over time.

An example of a motion.

Deformation gradient

The deformation gradient is given by

 \boldsymbol{F} = \frac{\partial \mathbf{x}}{\partial \boldsymbol{X}} \quad \implies \quad F_{ij} = \frac{\partial x_i}{\partial X_j}

Therefore

 \begin{align} F_{11} &= \frac{\partial x_1}{\partial X_1} = \cfrac{1}{4}\left[4 + (- 3 - X_2)~t\right] \ F_{12} &= \frac{\partial x_1}{\partial X_2} = \cfrac{1}{4}\left[(- 5 - X_1)~t\right] \ F_{21} &= \frac{\partial x_2}{\partial X_1} = 2~t \ F_{22} &= \frac{\partial x_2}{\partial X_2} = 1 \end{align}

At t = 1 at the position \boldsymbol{X} = (0,0) we have

 \mathbf{F} = \begin{bmatrix} \frac{\partial x_1}{\partial X_1} & \frac{\partial x_1}{\partial X_2} \ \frac{\partial x_2}{\partial X_1} & \frac{\partial x_2}{\partial X_2} \end{bmatrix} = \cfrac{1}{4} \begin{bmatrix} 1 & -5 \\ 8 & 4 \end{bmatrix}

You can calculate the deformation gradient at other points in a similar manner.

Right Cauchy-Green deformation tensor

We have

 \boldsymbol{C} = \boldsymbol{F}^T\cdot\boldsymbol{F}

Therefore,

 \mathbf{C} = \mathbf{F}^T~\mathbf{F} = \cfrac{1}{16} \begin{bmatrix} 65 & 27 \\ 27 & 41 \end{bmatrix}

To compute \boldsymbol{U} we have to find the eigenvalues and eigenvectors of \boldsymbol{C}. The eigenvalue problem is

 (\mathbf{C} - \lambda^2~\mathbf{I})\mathbf{N} = \mathbf{0}

where

 \mathbf{I} = \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix}

To find the eigenvalues we solve the characteristic equation

 \det(\mathbf{C} - \lambda^2~\mathbf{I}) = 0

Plugging in the numbers, we get

 \det\begin{bmatrix} \cfrac{65}{16} - \lambda^2 & \cfrac{27}{16} \ \cfrac{27}{16} & \cfrac{41}{16} - \lambda^2 \end{bmatrix} = 0

or

 \lambda^4 - \cfrac{53}{8}~\lambda^2 + \cfrac{121}{16} = 0

This equation has two solutions

 \begin{align} \lambda_1^2 & = \cfrac{53}{16} + \cfrac{3}{16}~\sqrt{97} = 5.159 \ \lambda_2^2 & = \cfrac{53}{16} - \cfrac{3}{16}~\sqrt{97} = 1.466 \end{align}

Taking the square roots we get the values of the principal stretches

 \lambda_1 = 2.2714 \qquad \lambda_2 = 1.2107

To compute the eigenvectors we plug into the eigenvalues into the eigenvalue problem to get

 \left\{ \begin{bmatrix} 65 & 27 \\ 27 & 41 \end{bmatrix} - \lambda^2_1 ~ \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix} \right\}~\begin{bmatrix} N_1^{(1)} \\ N_2^{(1)} \end{bmatrix} = \begin{bmatrix} 0 \\ 0 \end{bmatrix}

Because this system of equations is not linearly independent, we need another equation to solve this system of equations for N^{(1)}_1 and N^{(1)}_2. This problem is eliminated by using the following equation (which implies that \mathbf{N} is a unit vector)

 (N^{(1)}_2)^2 = \sqrt{1 - (N^{(1)}_1)^2}

Solving, we get

 \mathbf{N}_1 = \begin{bmatrix} N_1^{(1)} \\ N_2^{(1)} \end{bmatrix} = \begin{bmatrix} 0.8385 \\ 0.5449 \end{bmatrix}

We can do the same thing for the other eigenvector \mathbf{N}_2 to get

 \mathbf{N}_2 = \begin{bmatrix} N_1^{(2)} \\ N_2^{(2)} \end{bmatrix} = \begin{bmatrix} -0.5449 \\0.8385 \end{bmatrix}

Therefore,

 \boldsymbol{N}_1\otimes\boldsymbol{N}_1 = \mathbf{N}_1^T~\mathbf{N}_1 = \begin{bmatrix} 0.8385 & 0.5449 \end{bmatrix} \begin{bmatrix} 0.8385 \\ 0.5449 \end{bmatrix} = \begin{bmatrix} 0.7031 & 0.4569 \\ 0.4569 & 0.2969 \end{bmatrix}

and

 \boldsymbol{N}_2\otimes\boldsymbol{N}_2 = \mathbf{N}_2^T~\mathbf{N}_2 = \begin{bmatrix} -0.5449 & 0.8385 \end{bmatrix} \begin{bmatrix} -0.5449 \\0.8385 \end{bmatrix} = \begin{bmatrix} 0.2969 & -0.4569 \\ -0.4569 & 0.7031 \end{bmatrix}

Therefore,

 \boldsymbol{C} = \lambda_1^2~\boldsymbol{N}_1\otimes\boldsymbol{N}_1 + \lambda_2^2~\boldsymbol{N}_2\otimes\boldsymbol{N}_2 \quad \implies \quad \mathbf{C} = 5.159~ \begin{bmatrix} 0.7031 & 0.4569 \\ 0.4569 & 0.2969 \end{bmatrix} + 1.466~ \begin{bmatrix} 0.2969 & -0.4569 \\ -0.4569 & 0.7031 \end{bmatrix}

We usually don't see any problem to calculate \boldsymbol{C} at this point and go straight to the right stretch tensor.

Right stretch

The right stretch tensor \boldsymbol{U} is given by

 \boldsymbol{U} = \lambda_1~\boldsymbol{N}_1\otimes\boldsymbol{N}_1 + \lambda_2~\boldsymbol{N}_2\otimes\boldsymbol{N}_2 \quad \implies \quad \mathbf{U} = 2.2714~ \begin{bmatrix} 0.7031 & 0.4569 \\ 0.4569 & 0.2969 \end{bmatrix} + 1.2107~ \begin{bmatrix} 0.2969 & -0.4569 \\ -0.4569 & 0.7031 \end{bmatrix}

or

 \mathbf{U} = \begin{bmatrix} 1.9565 & 0.4846 \\ 0.4846 & 1.5256 \end{bmatrix}

We can invert this matrix to get

 \mathbf{U}^{-1} = \begin{bmatrix} 0.5548 & -0.1762 \\ -0.1762 & 0.7114 \end{bmatrix}

Rotation

We can now find the rotation matrix by using th relation

 \boldsymbol{R} = \boldsymbol{F}\cdot\boldsymbol{U}^{-1}

In matrix form,

 \mathbf{R} = \cfrac{1}{4} \begin{bmatrix} 1 & -5 \\ 8 & 4 \end{bmatrix} \begin{bmatrix} 0.5548 & -0.1762 \\ -0.1762 & 0.7114 \end{bmatrix} = \begin{bmatrix} 0.3590 & -0.9334 \\ 0.9334 & 0.3590 \end{bmatrix}

You can check whether this matrix is orthogonal by seeing whether \mathbf{R}~\mathbf{R}^T = \mathbf{R}^T~\mathbf{R} = \mathbf{I}.

You thus get the polar decomposition of \boldsymbol{F}. In an actual calculation you have to be careful about floating point errors. Otherwise you might not get a matrix that is orthogonal.


Advertisements






Got something to say? Make a comment.
Your name
Your email address
Message